2010
DOI: 10.1371/journal.pgen.1000911
|View full text |Cite
|
Sign up to set email alerts
|

The Five AhMTP1 Zinc Transporters Undergo Different Evolutionary Fates towards Adaptive Evolution to Zinc Tolerance in Arabidopsis halleri

Abstract: Gene duplication is a major mechanism facilitating adaptation to changing environments. From recent genomic analyses, the acquisition of zinc hypertolerance and hyperaccumulation characters discriminating Arabidopsis halleri from its zinc sensitive/non-accumulator closest relatives Arabidopsis lyrata and Arabidopsis thaliana was proposed to rely on duplication of genes controlling zinc transport or zinc tolerance. Metal Tolerance Protein 1 (MTP1) is one of these genes. It encodes a Zn2+/H+ antiporter involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
143
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(146 citation statements)
references
References 33 publications
2
143
0
1
Order By: Relevance
“…Indeed, some of the genes involved in metal tolerance (e.g. HMA4 and MTP1) have multiple copies in the A. halleri genome (Talke et al, 2006;Hanikenne et al, 2008;Shazad et al, 2013). Our data suggest that AhCAX1 is a single-copy gene in A. halleri and that differential expression between species can be attributed to cis-or transregulation.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, some of the genes involved in metal tolerance (e.g. HMA4 and MTP1) have multiple copies in the A. halleri genome (Talke et al, 2006;Hanikenne et al, 2008;Shazad et al, 2013). Our data suggest that AhCAX1 is a single-copy gene in A. halleri and that differential expression between species can be attributed to cis-or transregulation.…”
Section: Discussionmentioning
confidence: 73%
“…Third, higher activity of certain metal homeostasis genes in A. halleri appears to be at least partly due to gene copy number expansion. Examples are three tandem HMA4 copies (Hanikenne et al, 2008) and a total of up to five MTP1 paralogs present either in tandem or dispersed in the genome (Shahzad et al, 2010). Not all of these MTP1 paralogs contribute to higher transcript abundance in A. halleri (Drä ger et al, 2004;Shahzad et al, 2010) and thus have not all been detected by QTL analysis.…”
Section: Discussionmentioning
confidence: 99%
“…MTP1 transporters from different species of plants have been found to localize to the tonoplast and sequestrate Zn 2+ into vacuoles; over-expression of MTP1 gene can enhance zinc tolerance [12,[16][17][18][19]. Recently, it has been found that there are five duplications of MTP1 gene in Zn/Cd hyperaccumulator A. halleri and this could be a major basis of the zinc tolerance [20]. in leaves up to a maximum of 9 g kg À1 DW and also can accumulate Zn 2+ in shoots up to 2% of dry weight [21][22][23].…”
Section: Introductionmentioning
confidence: 99%